3' end structure of the human (2'-5') oligo A synthetase gene: prediction of two distinct proteins with cell type-specific expression. - Benech, P (1985)
Analysis of the sizes of the (2'-5') oligo A synthetase polyadenylated transcripts in various human cell lines by hybridization with a cDNA probe revealed that the pattern of the transcripts was cell-type specific. In order to investigate whether the 1.6 Kb, 1.8 Kb and 3.6 Kb mRNA, which are predominantly expressed in different cell-lines, encode different proteins or could differ in the size of their 3' or 5' untranslated sequences, the corresponding gene was isolated. On Southern blots of human genomic RNA, the cDNA probe hybridize to a 3.1 Kb EcoRI fragment. Three overlapping genomic clones were isolated which contain the same 3.1 Kb EcoRI fragment. Transcriptional mapping of the 3' end of the gene by Northern blots, hybridization translation experiments and sequencing showed that the 1.6 and 1.8 Kb mRNA are produced by a differential processing at the 3' end of the primary transcript of the same gene. The polyadenylation site of the 1.6 Kb mRNA is located 1.9 Kb upstream to the one of the 1.8 Kb mRNA. To produce the latter transcript, a portion of the last exon of the 1.6 Kb mRNA (including a segment coding for a very hydrophobic sequence of 18 amino acids and 3' untranslated sequence) is spliced out. The two mRNAs thus encode two different proteins which could have different affinity for cellular elements. The 3.6 Kb transcript has the same polyadenylation site as the 1.8 Kb mRNA, but contains additional unspliced 3' intron sequences.